PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA BERBASIS KOOPERATIF TIPE COURSE REVIEW HORAY (CRH) PADA MATERI MOMENTUM DAN IMPULS DI KELAS X SMA - Isnaini Sandy Harnum; Nur Islami; Yennita Yuanita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The learning device developed is a physics learning tool using a cooperative model type Course Review Horay (CRH) class X SMA on momentum and impulse material, consisting of a Learning Implementation Plan (RPP), Student Worksheets (LKPD), and cognitive learning outcome test instruments. . The purpose of this study was to produce a physics learning device using a cooperative model type Course Review Horay (CRH) which is valid in class X SMA on momentum and impulse material. This research is expected to be a reference for making innovative learning tools and can be used as a foundation in the teaching and learning process so that learning objectives can be achieved. This type of research is a Research and Development (R&D) using the 4D model. This research is only limited to the development stage. The research instrument used was the RPP validation assessment sheet, LKPD, and the cognitive learning outcome test instrument used by the validator to assess learning tools. The data analysis in this study used descriptive analysis, by calculating the validity score of each indicator of the learning device. The results showed that the physics learning device using the Course Review Horay (CRH) cooperative model was declared valid with the overall score of the device being 3.36 in the very high category, so it was declared feasible to be used for teaching in class X SMA on momentum and impulse material.Key Words: Physics Learning Tools, Cooperative Model of Course Review Horay type,Momentum and Impulse.